Professional soccer and skin temperature. (27th October 2018) - Pfab, F.
Abstract : Linked article: This is a commentary on D. Rodriguez‐Sanz et al., pp. 2020–2024 in this issue. To view this article visit https://doi.org/10.1111/jdv.14966